Descriptions of two new notodontid species from the relic Fagus forests in northeastern Taiwan (Lepidoptera, Notodontidae) - Wu, Shipher; Chang, Wei-Chun; Wang, Li-Hao; Huang, Chia-Lung; Hsu, Yu Feng (Zootaxa, 2016)
Two new Fagus-feeding notodontids, i.e. Syntypistis taipingshanensis Wu & Hsu sp. n. and Pheosiopsis seni Wu & Hsu sp. n. are recently discovered from the relic Fagus forests in northeastern Taiwan. Based on the genitalia structures, the closely relatives of two new species are S. melana Wu & Fang, 2003 and P. albalienata Kishida & Kobayashi, 2005, respectively, both occurring in the Fagus forests of Southern China.